Faktor-Faktor yang Mempengaruhi Kepatuhan Wajib Pajak Pemilik UMKM Pada Kantor Pelayanan Pajak Pratama Pekanbaru Senapelan - Rasmon, Rasmon; Sitinjak, Marnala; Rahayu, Eva Ulfah; Zubir, Zubir; Tinaria, Lisa (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2023)
The title of this research is "The Influence of Taxpayer Understanding, Use of NPWP, and Taxpayer Awareness on Taxpayer Compliance of MSME Owners at the Pekanbaru Senapelan Pratama Tax Service Office". This research was conducted because of the lack of taxpayer compliance in Indonesia. The purpose of this study was to determine the effect of taxpayer understanding, the benefits of NPWP, and taxpayer awareness on taxpayer compliance of MSME owners. This study uses multiple linear regression analysis techniques. The results of this study are that partially understanding of taxpayers affects taxpayer compliance of MSME owners while the benefits of NPWP, and taxpayer awareness do not affect taxpayer compliance of MSME owners at the Pekanbaru Pratama Senapelan Tax Service Office. Simultaneously the understanding of taxpayers, the benefits of NPWP, and awareness of taxpayers has no effect on taxpayer compliance of MSME owners at the Pekanbaru Senapelan Pratama Tax Service Offic